A support vector machine‐based VVP wind retrieval method. (13th February 2015) - Li, Nan; Wei, Ming; Mu, Xiyu; Zhao, Chang
Abstract Velocity volume processing (VVP) is a common wind retrieval method for single‐Doppler radar. However, hindered by the problem of the ill‐conditioned coefficient matrix, VVP method has not been applied effectively. In this paper, a support vector machine‐based VVP (SVM VVP) method is proposed to improve the VVP method. SVM VVP retrieves wind field through constructing a support vector regression machine for the radial velocity. The new method is applied to a real case, and the retrieval shows that SVM VVP can give accurate and high‐resolution results. It is helpful for studying wind fields of small‐scale precipitation systems.